A GREEN STRATEGY TO SYNTHESIZE ENVIRONMENT FRIENDLY METAL OXIDE NANOPARTICLES FOR POTENTIAL APPLICATIONS – A REVIEW - P, VANI; N, MANIKANDAN; G, VINITHA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Chemical reducing and capping reagents are largely used in synthesizing metal oxide nanoparticles which limits the biomedical applications. Researchers have recently found out the eco-friendly technique of green synthesis which enhances the unique physical and chemical properties of nanomaterials. In this critique, we discuss green route to synthesize metal oxide nanoparticles and its significant applications in various fields of energy and environment, aerospace, medicine, biotechnology, etc.This study arouses to provoke new research design of approach to synthesize nanoparticles for various technological applications. In this review, most of the metal oxides nanoparticles with different plant extract with enhanced properties for its potential applications are discussed which confirms plant extracts as a potential candidate to be used as reducing and capping agent.